Risk factors for injury in a community‐treated cohort of patients with epilepsy in Australia. (5th February 2019) - Tan, Michael; Boston, Ray; Cook, Mark J.; D'Souza, Wendyl J.
Summary: Objective: There remains a paucity of knowledge regarding specific epilepsy‐related risk factors for accidents and injuries in people with epilepsy. Injury studies in people with epilepsy are overrepresented, with tertiary based populations that are prone to bias from severe disease. This study aims to assess the contribution of epilepsy‐related risk factors to injuries in a community‐based cohort. Methods: We performed a retrospective nested case‐control study on patients recruited into the Tasmanian Epilepsy Register (TER) from July 1, 2001 to June 30, 2002. The TER is a community‐based cohort of patients with epilepsy in Tasmania, Australia, recruited from the national prescription database and interviewed for epilepsy diagnosis, injuries, and risk factors using validated questionnaires with diagnosis made by an epilepsy specialist. The primary outcome measures were lifetime and recent 12‐month injury. Multivariate logistic regression with multiple imputation modeling responder nondisclosure was performed, adjusting for age, gender, region, socioeconomic status, seizure frequency, and epilepsy duration. Results: A total of 819 patients with epilepsy were included in this study. Ten percent of patients experienced an injury in the preceding year. Before adjusting for seizure frequency, any seizure over the past 12 months was associated with recent injury (adjusted odds ratio [OR] = 7.90, 95% confidence interval [CI] = 4.17‐14.96). Impaired awareness, cluster seizures, sleep‐only seizures, and convulsive seizure were characteristics found to significantly influence injuries irrespective of seizure frequency. Although a warning appeared initially protective for recent injuries (OR = 0.39, 95% CI = 0.22‐0.69), this was entirely explained by seizure frequency, with the effect becoming nonsignificant. Significance: Likely due to their unpredictable nature, seizures expose patients with epilepsy to a high risk of life‐threatening injury. These findings emphasize the importance of seizure freedom for maximizing the safety of patients with epilepsy.